Correlates of functional capacity among centenarians - Martin, Peter; MacDonald, Maurice; Margrett, Jennifer; Siegler, Ilene C.; Poon, Leonard W. (My University, 2013)
This study investigated correlates of functional capacity among participants of the Georgia Centenarian Study. Six domains (demographics and health, positive and negative affect, personality, social and economic support, life events and coping, distal influences) were related to functional capacity for 234 centenarians and near centenarians (i.e., 98 years and older). Data were provided by proxy informants. Domain-specific multiple regression analyses suggested that younger centenarians, those living in the community and rated to be in better health were more likely to have higher functional capacity scores. Higher scores in positive affect, conscientiousness, social provisions, religious coping, and engaged life style were also associated with higher levels of functional capacity. The results suggest that functional capacity levels continue to be associated with age after 100 years of life and that positive affect levels and past life-style activities as reported by proxies are salient factors of adaptation in very late life.
Keywords: Centenarians; Functional capacity; Psychosocial resources